Research and Application of Flue Gas Waste Heat Recovery in Co-generation Based on Absorption Heat-exchange. (2016) - Li, Feng; Duanmu, Lin; Fu, Lin; Zhao, Xi ling
Abstract: For gas cogeneration system, there are problems to be solved. There is great heat transfer temperature difference in the heat-exchange progress. It can cause huge irreversible loss of heat transfer. More seriously, exhaust temperature of flue gas is generally more than 90°C. The part of the heat is equal to the 40 percent of heating load. The return water conventionally has a high temperature, so the flue gas waste heat is difficult to recover. Based on the situation, this paper introduced the technique of flue gas waste heat recovery in gas cogeneration based on absorption heat-exchange. Absorption heat-exchange units are set up in thermal station to lower temperature of water in heat network to about 20°C. The return water is heated orderly by gas-water heat exchanger, absorption heat pump and the peak load heater. Compared with the traditional systems, this system runs with a greater circuit temperature drop so that the delivery capacity of the heat network increases dramatically. The heating capacity and the energy efficiency of the cogeneration plant is increased by the exhausted heat recovery from the flue gas. Finally, this paper has analyzed the advantages on energy-saving benefit, environmental benefit and economic benefit by one example that a gas cogeneration plant is reformed using the technology.